CONSUMPTION FISH POLYCULTURE USING AQUAPONIC (POLYPONIC) SYSTEM AT UPR MANDIRI ABADI PALEMBANG CITY - Raudhatus Sa’adah; Madyasta Anggana Rarassari; Eka Nurriza Kahirunnisa (Jurnal Perikanan Unram, 2024)
Stunting, known as short toddlers, is a long-term nutritional problem caused by low food intake over a long period of time. Stunting can occur when the fetus is in the womb and only becomes visible when the child is two years old. One of the initiatives promoted by the government is the fish eating movement and the program to increase aquaculture production, which contributes greatly to national food security, employment and the Indonesian economy. Fish is very rich in nutrients and beneficial for the body because it contains 18% protein consisting of EPA, essential amino acids, DHA, vitamins A, B1, B2, and D, as well as minerals. Polyculture is cultivation with 2 types of fish, where in 1 cultivation container you can raise each type of fish. Polyculture of betok fish and tilapia using an aquaponic system for 30 days with a stocking density of 40 m-2 betok fish and 40 m-2 tilapia fish resulted in a survival of betok fish of 95%, a length growth of 0.92 cm, a weight growth of 0 .76 g and the feed efficiency value is 27.2%, while the survival rate for tilapia is 97.5%, length growth is 1.75 cm, weight growth is 1.61 g. The height of lettuce varies between 9-11 cm with 2-3 leaves per plant. The quality of maintenance water, whether control or maintenance with treatment, is still within the optimum range for polyculture aquaponic systems.